2021
DOI: 10.5194/tc-15-1157-2021
|View full text |Cite
|
Sign up to set email alerts
|

The case of a southern European glacier which survived Roman and medieval warm periods but is disappearing under recent warming

Abstract: Abstract. Mountain glaciers have generally experienced an accelerated retreat over the last 3 decades as a rapid response to current global warming. However, the response to previous warm periods in the Holocene is not well-described for glaciers of the southern Europe mountain ranges, such as the Pyrenees. The situation during the Medieval Climate Anomaly (900–1300 CE) is particularly relevant since it is not certain whether the southern European glaciers just experienced significant ice loss or whether they … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 63 publications
2
15
0
3
Order By: Relevance
“…Therefore, whereas the projected increase in air temperature in mountain areas would result in enhanced mass loss for surface glaciers, the same rising temperatures might only marginally affect ice volume changes in caves. Monitoring studies in ice caves has been done sporadically since the mid-20th century (Racovita, 1994;Luetscher et al, 2005;Perşoiu and Pazdur, 2011;Kern and Perşoiu, 2013;Munroe, 2021), the results showing that reduction in winter precipitation and increase in winter temperatures are the main drivers behind loss of ice, with summer temperatures having a negligible role. Additionally, studies of perennial ice deposits in caves in Norway, Romania and Switzerland have suggested that above-average summer precipitation might play an important role in the overall volume changes in cave glaciers (Stoffel et al, 2009;Feurdean et al, 2011;Lauritzen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, whereas the projected increase in air temperature in mountain areas would result in enhanced mass loss for surface glaciers, the same rising temperatures might only marginally affect ice volume changes in caves. Monitoring studies in ice caves has been done sporadically since the mid-20th century (Racovita, 1994;Luetscher et al, 2005;Perşoiu and Pazdur, 2011;Kern and Perşoiu, 2013;Munroe, 2021), the results showing that reduction in winter precipitation and increase in winter temperatures are the main drivers behind loss of ice, with summer temperatures having a negligible role. Additionally, studies of perennial ice deposits in caves in Norway, Romania and Switzerland have suggested that above-average summer precipitation might play an important role in the overall volume changes in cave glaciers (Stoffel et al, 2009;Feurdean et al, 2011;Lauritzen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Están también bien identificadas, geomorfológicamente, las dos morrenas de la Pequeña Edad del Hielo (PEH) (García-Ruiz et al, 2014) pero, sin embargo, se desconoce la respuesta del glaciar a periodos cálidos anteriores como el Periodo Romano (500 BCE-400 años CE) o la Anomalía Climática Medieval (MCA, 900 -1300 años CE). Responder a la pregunta de qué extensión tenía el glaciar en esos periodos, e incluso determinar si había llegado a desaparecer completamente alguna vez, fue el principal objetivo del estudio y tenía que ser resuelto con la datación del hielo presente hoy en el glaciar (Moreno et al, 2021).…”
Section: El Glaciar De Monte Perdidounclassified
“…En gris, se muestra un intervalo donde la acumulación de hielo fue especialmente baja, predominando los procesos de fusión. Modificada de Moreno et al, (2021). 2), obtained using the Clam software (Blaauw, 2010;Blaauw et al, 2019).…”
Section: El Glaciar De Monte Perdidounclassified
See 2 more Smart Citations